Bridge inspection, evaluation and maintenance, within the Greek framework: Challenges and prospectives - Lampropoulos, Kyriakos; Moropoulou, Antonia; Mouzakis, Charalampos; Sapountzakis, Evangelos; Georgopoulos, Andreas; Sotiropoulos, Pavlos; Salakidis, Antonios; Tsilimantou, Elisavet (Technical Annals, 2025)
Bridges are invaluable elements of European transportation infrastructure. Inspection, evaluation and maintenance are key processes for the safe operation, efficient management and improved resilience of bridges. The relevant legislation for the systematic implementation of these processes is reviewed, as it sets the basis for addressing lasting challenges faced by the national bridge stock. The establishment of central data repositories and the gradual implementation of real time structural health monitoring on certain bridges of the national stock aim to improve the safety of bridges and contribute to the optimized utilization of the limited technical and financial resources for bridge management and maintenance. The national-specific limiting factors are analyzed, which hinder the direct adaptation of international expertise. The key drivers towards an enhanced inspection, evaluation and maintenance methodology are described, focusing on an expanded preliminary inspection of the bridge and its environment; state-of-the-art documentation methods and approaches; non-destructive assessment of the bridge structure, its environment and the bridge-environment interaction; assessment of the static, dynamic and seismic behavior of the bridge. Finally, the potential and limitations of both Building Information Modeling (BIM) and Bridge Information Modeling (BrIM) are briefly discussed in this work.